(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Hepatitis B virus (HBV) is a significant global health issue, affecting approximately 350 million chronic carriers worldwide. A retrospective study on HBV was conducted at the Maiduguri State Specialist Hospital from 2017 to 2023, utilizing laboratory records to evaluate the prevalence of HBV among patients. The analysis, performed using SPSS version 23.0, examined 81,469 patient records. Latex agglutination assays were employed to test for the presence of HBV surface antigen (HBsAg). The overall prevalence of HBV was found to be 3.89% (3,171 out of 81,469), with the highest prevalence occurring in 2018 at 5.01%. The infection rates were notably higher among females (57.2%) compared to males (42.8%). Additionally, the prevalence was slightly elevated during the dry season (3.91%) in contrast to the wet season (3.88%). There was significant (p<0.05) association between age, years and HBV prevalence. HBV is endemic in Maiduguri, exhibiting variations based on sex and seasonal factors. The study recommends enhanced vaccination and screening efforts.